2019
DOI: 10.18203/2349-3933.ijam20191155
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of patients presented with esophageal carcinoma in tertiary care teaching medical college of Gujarat, India

Abstract: Background: Esophageal cancer is associated with multiple risk factors and associated with poor prognosis. Incidence of Esophageal cancer is increases now a days and it became a sixth leading cause of cancer related death in world. The purpose of this study was to know the clinical profile of patients of esophageal cancer in a tertiary care teaching hospital of Gujrat, India.Methods: This is a retrospective hospital record based study for a period of 2015 to 2018 in which 103 patients with endoscopic biopsy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
4
4
0
Order By: Relevance
“…In our study majority (approximately 70%) of patients were in the age group of 50 years and above. [12,13] Similar finding were reported by study conducted by Kumar S et al where nearly three fourth of patients belongs to age group of above 50 yrs.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In our study majority (approximately 70%) of patients were in the age group of 50 years and above. [12,13] Similar finding were reported by study conducted by Kumar S et al where nearly three fourth of patients belongs to age group of above 50 yrs.…”
Section: Discussionsupporting
confidence: 85%
“…Approximately 50% cases of esophageal cancers are ADCs in Western countries in contrast, SCC continues to be the dominant type in other areas of the world, especially in Asia. [18] Similar findings were reported by Kumar et al, [12] from Gujarat, India where 75.8% of cases had SCC.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Dysphagia and loss of weight were common manifestations of esophageal cancers in our cohort, similar to findings by Mchembe et al in Tanzania [32] and Gibbs [37]. A study of esophageal cancer at a tertiary care teaching college in India al found that dysphagia was the most common symptom (86%) [38].…”
Section: Esophageal Cancersupporting
confidence: 90%